1993
DOI: 10.1007/bf01957219
|View full text |Cite
|
Sign up to set email alerts
|

Extended deep vein and inferior vena cava thrombosis in a 15-year-old boy: Successful lysis with recombinant tissue-type plasminogen activator 2 weeks after onset of symptoms

Abstract: We present the case of a 15-year-old boy with thrombosis of the inferior vena cava, the femoral, inguinal, and renal veins of unknown origin. Although the thrombosis was 2 weeks old, thrombolytic therapy with recombinant tissue-type plasminogen activator (maximum dosage: 0.4 mg/kg/h) was started as this appeared to be the only change to re-establish normal kidney function. After 1 week, treatment was discontinued because of generalized bleeding. At this time, the infrarenal inferior vena cava was again patent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The increased expression of P-selectin can lead to the occurrence of thrombophilia, inducing the activation of procoagulants and formation of fibrin ( 22 , 23 ). Studies ( 7 , 24 ) have revealed that P-selectin has a significant effect on thrombosis, where the upregulation of soluble P-selectin in the blood can be used as a clinical risk factor in venous thrombosis. Treatment of the HUVECs with IL-18 significantly increased the expression of P-selectin, unlike vWF, and its abnormal expression was effectively suppressed following inhibition of the activation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased expression of P-selectin can lead to the occurrence of thrombophilia, inducing the activation of procoagulants and formation of fibrin ( 22 , 23 ). Studies ( 7 , 24 ) have revealed that P-selectin has a significant effect on thrombosis, where the upregulation of soluble P-selectin in the blood can be used as a clinical risk factor in venous thrombosis. Treatment of the HUVECs with IL-18 significantly increased the expression of P-selectin, unlike vWF, and its abnormal expression was effectively suppressed following inhibition of the activation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…The t-PA can activate the plasminogen present on the fibrin surface, having a fibrinolytic effect locally ( 25 ). Recombinant t-PA synthesized by genetic engineering has been used as an antithrombotic drug ( 24 ). In the present study, it was found that IL-18 led HUVECs to produce t-PA, which significantly improved following the application of inhibitors of NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although thrombolysis is a treatment option for mesenteric venous thrombosis, it is not yet widely used: only a few case reports have been published (Table 1) [19–30] demonstrating a wide variety of strategies. Two recent review articles on mesenteric venous thrombosis fail to mention thrombolysis as a therapeutic option [6,7].…”
Section: Discussionmentioning
confidence: 99%